Arctic Hysteria and Other Strange Northern Emotions - Rossi, Riikka; Kankkunen, Sarianna; Nykänen, Elise (Finnish Literature Society / SKS, 2024)
Arctic Hysteria and Other Strange Northern Emotions: Case Studies in Finnish Literature opens a new perspective on the thriving area of research on the imagined North by studying emotions in the light of case studies in Finnish literature. The volume addresses the cultural history of Arctic hysteria and maps other strange emotions depicted and evoked in literature of the Finnish North. The volume comprises seven case studies which range from the works of internationally renowned authors, such as Rosa Liksom, Emmi Itäranta and Tove Jansson, to the affectively controversial and provocative writings of Timo K. Mukka, Marko Tapio and Pentti Linkola. Drawing from the study of the imagined North and theories and tools in the study of literature and emotions, the analyses show how such moods as melancholia, ecstasy or a peculiar sense of November are generated in texts and how literary emotions entangle with the Northern environment they depict. By focusing on the imagined North in Finnish modernism and contemporary literature, the authors offer original views on experiences of late modernity merging with the changing Northern environment in the age of the Anthropocene.